Farmer’s subjective elicited water response function for intensive olives and compromise programming method for irrigation supply decision - Berbel, Julio; Gutiérrez-Martín, Carlos (Economía agraría y recursos naturales (Internet), 2015)
This research analyses the subjective crop yield-water relationship and proposes a method to determine water supply in irrigated olives. The probability density for water response functions (PDF) is elicited from a series of interviews carried out on a wide group of farmers. The elicitation technique is based upon the triangular distribution (highest possible, most frequent and lowest possible) and estimates of yield related to water supply (low, ‘normal’ and full irrigation). The model presented illustrates the possibility of implementing simple decision models to support farmers to manage water considering the objectives of maximizing profit and minimizing risk.